2005
DOI: 10.1117/12.633102
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation and dynamics of bubbles forming around laser heated microabsorbers

Abstract: Selective tissue damage on the cellular level can be achieved due to transient microbubbles around laser-heated intracellular pigments. We investigated bubble dynamics and nucleation mechanisms at microabsorbers in suspensions as well as bubble formation in retinal pigment epithelial cells by fast flash photography and time-resolved probe laser transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…The high peak temperatures occurring at the melanosomes during irradiation lead to short living microbubbles which mechanically disrupt the RPE cells due to a short but strong volume increase [21]. Moreover, it could be observed that the radiant exposure and thus the energy required for bubble formation decreases with pulse duration [22].…”
Section: Introductionmentioning
confidence: 99%
“…The high peak temperatures occurring at the melanosomes during irradiation lead to short living microbubbles which mechanically disrupt the RPE cells due to a short but strong volume increase [21]. Moreover, it could be observed that the radiant exposure and thus the energy required for bubble formation decreases with pulse duration [22].…”
Section: Introductionmentioning
confidence: 99%
“…The results of Brinkmann et al 39 using single porcine melanosomes show that the 'origin of RPE cell damage for single pulse irradiation up to pulse durations of 3 ms can be described by a damage mechanism in which microbubbles around the melanosomes cause a rupture of the cell structure'. 39 In the following years research on the microbubble formation and the damage mechanism itself, 40,41 the detection of the laser-induced microbubbles 42 or damage thresholds caused by microbubble formation 13,40,43 was performed. A retinal in-vitro model was developed and cultured cells were irridiated by Denton et al 44,45 with different wavelength scenarios.…”
Section: History and State Of The Artmentioning
confidence: 99%
“…The performance of SRT relies on spatial and temporal confinement which reduces the energy required to achieve the same result without affecting neighbored layers when the laser operates with a pulse length shorter than the thermal relaxation time of the RPE of 10 µs [30]. During this process, the structural integrity of RPE cells is destroyed by fast expanding and collapsing microbubbles which are formed around laser heated intracellular pigments [34][35][36]. Although the precise biological effects, especially caused by sub-lethal cellular irradiation, still need to be evaluated clinically, it is certain that cell-wall rupture leads to cell death.…”
Section: Introductionmentioning
confidence: 99%